Maternal outcome of prenatally diagnosed lethal fetal anomalies: a year review - Abdulwahab, Dalia F; S.L., Yong; Ismail, Hamizah; Awang, Mokhtar; Nusee, Zalina; Ismail, Rozihan (Elsevier BV, 2012)
Objectives: To determine maternal morbidities in relation to prenatal diagnosis of lethal fetal anomalies and termination of pregnancy (TOP). Materials: Twenty five patients with prenatal diagnosis of lethal fetal anomalies in Hospital Tengku Ampuan Afzan, Kuantan, Malaysia. Methods: This was a retrospective review in Hospital Tengku Ampuan Afzan, Kuantan, Malaysia in the year of 2011. All patients diagnosed prenatally to carry lethal fetal anomalies was reviewed. Data regarding maternal morbidities and outcome was collected from patients’ case note in the hospital record office. Analysis was done by using SPSS version 17.0. Results: Twenty five pregnant patients were diagnosed with lethal fetal anomalies via ultrasound with or without genetic study. The patients’ mean age was 29.9±6.3 years old. The mean gestational age at diagnosis of lethal fetal anomalies and at TOP or delivery were 26.5±7.4 and 28.7±7.8 weeks respectively. The lethal fetal anomalies included fetuses with multiple structural abnormalities (40%), anencephaly or severe encephalocele (32%), non-immune hydrops fetalis (16%) and syndromic fetuses (12%) i.e. Pentalogy of Cantrell and Edward’s syndrome. Seven (28%) patients had early counseling and TOP at the gestation of <22 weeks. Beyond 22 weeks gestation, 8 (32%) patients had TOP and 10 (40%) patients had spontaneous delivery. Twenty (80%) patients delivered or aborted vaginally, 3 (12%) patients with assisted breech delivery, and 2 (8%) patients with abdominal delivery. The abdominal deliveries were for transverse lie in labour and emergency hysterotomy for failed induction complicated by hysterectomy due to intraoperative finding of ruptured uterus. Overall, the associated adverse events included abnormal lie during delivery (16%), symptomatic polyhydramnios requiring amnioreduction (16%), post-partum haemorrhage (12%), retained placenta (12%), blood transfusion (8%), uterine rupture (4%) and endometritis (4%). Mean duration of hospital stay was 6.6±3.7 days. Conclusions: Prenatal diagnosis and TOP at an early gestation may reduce maternal morbidities and improve the outcome